Genome-wide Investigation of microRNAs and Their Targets in Brassica rapa ssp. pekinensis Root with Plasmodiophora brassicae Infection - Xiaochun Wei; Wen Xu; Yuxiang Yuan; Qiuju Yao; Yanyan Zhao; Zhiyong Wang; Wusheng Jiang; Xiaowei Zhang (Horticultural Plant Journal, 2016)
Increasing evidence has revealed that microRNAs play a pivotal role in the post transcriptional regulation of gene expression in response to pathogens in plants. However, there is little information available about the expression patterns of miRNAs and their targets in Chinese cabbage (Brassica rapa ssp. pekinensis) under Plasmodiophora brassicae stress. In the present study, using deep sequencing and degradome analysis, a genome-wide identification of miRNAs and their targets during P. brassicae stress was performed. A total of 221 known and 93 potentially novel miRNAs were successfully identified from two root libraries of one control (635-10CK) and P. brassicae-treated Chinese cabbage samples (635-10T). Of these, 14 known and 10 potentially novel miRNAs were found to be differentially expressed after P. brassicae treatment. Degradome analysis revealed that the 223 target genes of the 75 miRNAs could be potentially cleaved. KEGG (Kyoto Encyclopedia of Genes and Genomes) pathway analysis suggested that the putative target genes of the miRNAs were predominately involved in selenocompound metabolism and plant hormone signal transduction. Then the expression of 12 miRNAs was validated by quantitative real-time PCR (qRT-PCR). These results provide insights into the miRNA-mediated regulatory networks underlying the stress response to the plant pathogen P. brassicae.